Blood Transfusion Strategy in Gastrointestinal Tract Bleeding: Liberal or Restrictive - Ummi Ulfah Madina; Murdani Abdullah (The Indonesian Society for Digestive Endoscopy, 2014)
Gastrointestinal tract bleeding is an emergency problem, which is frequently found. The manifestations of gastrointestinal tract bleeding vary, ranging from massive bleeding which is life threatening until occult bleeding that is not sensed by the patient. One of the main objectives in the management of gastrointestinal tract bleeding is stabilizing patient’s hemodynamic, either by using infusion of crystalloid, colloid, or even with the administration of blood transfusion. In massive gastrointestinal tract bleeding, administration of red blood cells transfusion may be life saving. However, in cases where bleeding is not profuse, the safest and most effective blood transfusion strategy is still controversial. Until now, there is no trial that gives information regarding safety and effectiveness of liberal or restrictive transfusion strategy in lower gastrointestinal tract bleeding. However, for most patients with gastrointestinal bleeding, with or without portal hypertension, it is better to postpone blood transfusion until the hemoglobin level decrease to less than 7 g/dL.Keywords: gastrointestinal tract bleeding, blood transfusion, liberal, restrictive